Pengadaan Bazar Sebagai Upaya Meningkatkan Pendapatan Usaha Mikro, Kecil, Menengah (UMKM) Di Desa Sindon - Lailla Syaharany; Desi Anggraini; Anggit Dyah Kusumastuti; Annisa Indah Mutiasari (Fakultas Teknik Universitas Cenderawasih, 2023)
UMKM are productive businesses owned by individuals and/or individual business entities that meet the criteria for micro businesses as regulated in law. The government supports UMKM with programs as an effort to improve community welfare. The government's efforts to improve community welfare are through the National Economic Recovery (PEN) program supporting UMKM. The Sindon Bazaar is a forum for Sindon Village UMKM which was formed by the Sindon Gemah Abundant KKN Committee Team (SGM). This bazaar was held according to the needs and potential of the community in Sindon Village. The management of the Sindon Bazaar consists of the SGM KKN Committee Team assisted by the youth of the local Dukuh Youth Organization. In the Sindon Bazaar, there are many UMKM selling various foods, drinks and toys for children. The results of the implementation of the bazaar that have been achieved include increasing the income of the UMKM community who participated in the bazaar, where what was usually empty of consumers became busy with consumers and the level of sales increased, as well as helping the people of Sindon Village to innovate and hone their skills as a new business opportunity